Struktur dan Unsur Kebahasaan Teks Cerita Fantasi Siswa Kelas VII SMPN 1 Tanjuang Baru - Putri, Adira Intania; Tamsin, Andria Catri (TSAQOFAH, 2023)
This type of research is a qualitative research with descriptive method. This research was conducted at SMPN 1 Tanjung Baru. The instrument in this study uses a test. Data collection techniques with data research in this study by means of documentation and table instruments. Checking or checking the entire data using data triangulation. Based on the research results, it can be concluded two things. These two things are as follows. First, in writing fantasy story texts, class VII UPT SMP Negeri 1 Tanjuang Baru students have not used the text structure properly. Second, when viewed from the language in the text of fantasy stories for class VII UPTSMP Negeri 1 Tanjuang Baru students, there are still many errors found.